2014
DOI: 10.1146/annurev-physiol-020911-153251
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Absorption of Folates

Abstract: The properties of intestinal folate absorption were documented decades ago. However, it was only recently that the proton-coupled folate transporter (PCFT) was identified and its critical role in folate transport across the apical brush-border membrane of the proximal small intestine established by the loss-of-function mutations identified in the PCFT gene in subjects with hereditary folate malabsorption and, more recently, by the Pcft-null mouse. This article reviews the current understanding of the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
126
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(128 citation statements)
references
References 129 publications
1
126
0
1
Order By: Relevance
“…Although human proton-coupled folate transporter plays a key role in the intestinal absorption of folic acid (Visentin et al, 2014), Urquhart et al (2010) reported that human proton-coupled folate transporter mRNA levels decreased in patients receiving PPIs. Thus, it is likely that the decreased oral absorption of folic acid caused by PPIs contributed to the development of hematologic toxicity associated with pemetrexed; however, we demonstrated that the coadministration of other PPIs was not a significant risk factor for hematologic toxicity associated with pemetrexed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although human proton-coupled folate transporter plays a key role in the intestinal absorption of folic acid (Visentin et al, 2014), Urquhart et al (2010) reported that human proton-coupled folate transporter mRNA levels decreased in patients receiving PPIs. Thus, it is likely that the decreased oral absorption of folic acid caused by PPIs contributed to the development of hematologic toxicity associated with pemetrexed; however, we demonstrated that the coadministration of other PPIs was not a significant risk factor for hematologic toxicity associated with pemetrexed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…RFC acts at a physiological pH in the distal small intestine and the colon, whereas PCFT mediates the intestinal absorption of dietary folates at acidic pH in the proximal half of the small intestine [3]. After intestinal uptake, most of the folate is reduced and methylated and enters the circulation mainly as 5-MTHF.…”
Section: Folate Transport and Metabolismmentioning
confidence: 99%
“…Mammals meet their biosynthetic needs for one-carbon donors by absorption of dietary folates mediated by the protoncoupled folate transporter (PCFT) 2 (SLC46A1) (1,2). Mutations in the PCFT gene that result in loss of the protein or its function are the basis for hereditary folate malabsorption (OMIM 229050), a rare autosomal recessive disorder (1,3).…”
mentioning
confidence: 99%